An intercultural study of euphemistic strategies used in Saudi Arabic and American English - Al-Khasawneh, Fadi (Universitas Pendidikan Indonesia, 2018)
People often use euphemistic utterances or expressions to avoid offensive or tabooed topics, to make them more implicit and considerate. This paper explores the euphemistic strategies used in Saudi Arabic and American English. The sample of this study includes 145 college students (78 Saudis and 67 Americans). A questionnaire adopted from Rabab’ah and Al-Qarni (2012) was used to collect the data of the present study. The results revealed various strategies used by the participants, such as deletion, synonyms, metaphor, understatement, part-for-whole, overstatement, and jargons. The most frequent strategies used by the Saudis were ‘part-for-whole’, ‘understatement’, and ‘general- for-specific’. The American participants tended to use ‘taboo words’, ‘general-for-specific’ and ‘synonyms’ more frequently than the other strategies. The findings also showed that there is no relationship between strategy choice and gender. The findings suggest that Saudi Arabic seems to use euphemistic strategies more than the Americans. These results could be referred to cultural and religious beliefs and values. The study recommends raising the awareness of euphemism strategies for more active communication.